Microfinance as a Catalyst for Women’s Empowerment in India - Kanodia, Vishal (Journal of Economics and Management, 2025)
In developing nations, there's significant focus on empowering women, recognizing its vital role in poverty alleviation and overall development. Microfinance institutions have become essential tools in the fight against poverty, particularly with regard to women's empowerment. Microfinance has been shown to have good benefits on raising income levels, financial empowerment, economic empowerment, social empowerment, political empowerment, encouraging entrepreneurship, and fostering social inclusion, this paper attempts to know the advantage of microfinance in empowering women and to know the trends of savings and loan outstanding by SHG-BLP. This paper is exploratory in nature.